Implementation of Multilayer Perceptron for OFDM Power-Line Communication - Vijayan, T.; Abinethri,; Kalaiselvi, B. (International Journal of Psychosocial Rehabilitation, 2018)
A high-speed data-communication over low-voltage power line has become a hot research topic for electrical advancements in recent years. Power-line communication (PLC), based on orthogonal frequency-division multiplexing (OFDM), is developing rapidly. OFDM is used for high speed data communications. However, it is unable to deal with the orthogonality degradation between the sub channels due to the time-variant characteristics of the multipath power-line channels, which is known as the Inter Channel Interference (ICI) problem. In this paper we propose a nonlinear equalizer based on Multilayer Perceptron trained with a mean square error (MSE) criterion to eliminate the ICI. In this paper first linear equalizer is designed with LMS algorithm. We compare the performance of linear equalizer and nonlinear equalizer based on constellation error probability.